Flexible Teaching and Learning Modalities in Undergraduate Science Amid the COVID-19 Pandemic - Anderton, Ryan S.; Vitali, Julian; Blackmore, Conner; Bakeberg, Megan C. (Frontiers in Education, 2021)
Since the first case of the novel coronavirus emerged in late 2019 (COVID-19), it quickly spread beyond China, with reported cases in nearly all countries and territories. As these unprecedented times have resulted in significant social and economic disruption, educational institutions have been forced to implement alternative teaching and learning approaches, including a total transition to online learning. Given the dependence of undergraduate science units and degrees on practical and laboratory activities, students and academics are faced with significant hurdles regarding delivery, learning, and assessment. Therefore, this article considers the impact of COVID-19 and the approaches being utilised to facilitate undergraduate science learning during the evolving pandemic.